2020
DOI: 10.1108/ec-03-2020-0160
|View full text |Cite
|
Sign up to set email alerts
|

Effect of journal misalignment on the static characteristics of an innovative journal bearing with adjustable elements in load-on-pad and load-between-pad configurations

Abstract: Purpose The purpose of this paper is to theoretically analyze an innovative form of variable bearing configuration having four pads with unique adjustability principle operated under journal misaligned conditions. The parameters such as load positions, degrees of misalignment (DM) and pad adjustment configurations influencing the steady-state performance of the four-pad adjustable bearing are detailed in this paper. Design/methodology/approach The proposed adjustable pad geometry possesses the ability to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…With the development of computer and testing technology, the problems of tilting pad bearings in practical applications are found, dealt with and a new model to solve the problem is established. The mathematical model of fluid lubrication of tilting pad bearings is developed from a simple two-dimensional thermo hydrodynamic analysis model to a complex three-dimensional thermo hydrodynamic analysis model, and further to a complex three-dimensional thermoelastic hydrodynamic analysis model, whose computational accuracy and speed have been continuously improved [6] [7] .The effects of turbulence effect [19] [20] , rotor tilting and misalignment [17] [18] , and cavitation effect on the bearing performance such as power consumption, lubrication characteristics, temperature rise of bearing shell, and dynamic characteristics at high speeds are also considered in the theoretical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of computer and testing technology, the problems of tilting pad bearings in practical applications are found, dealt with and a new model to solve the problem is established. The mathematical model of fluid lubrication of tilting pad bearings is developed from a simple two-dimensional thermo hydrodynamic analysis model to a complex three-dimensional thermo hydrodynamic analysis model, and further to a complex three-dimensional thermoelastic hydrodynamic analysis model, whose computational accuracy and speed have been continuously improved [6] [7] .The effects of turbulence effect [19] [20] , rotor tilting and misalignment [17] [18] , and cavitation effect on the bearing performance such as power consumption, lubrication characteristics, temperature rise of bearing shell, and dynamic characteristics at high speeds are also considered in the theoretical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Jiaojiao's simulation and experimental studies showed that the effect of non-Gaussian roughness characteristics on the bearing performance was greater than that of misalignment. Girish and Pai [27] proposed an adjustable pads bearing model for the study of bearing misalignment, and the study emphasized the importance of the bearing misalignment factor, revealing that the peak pressure of the oil film generated at both ends of the pads at a higher misalignment was the key factor for the increase of bearing load carrying capacity. the proposed model could resist journal misalignment and improve bearing performance.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 4 investigated the effect of journal axial motion on the lubrication characteristics of tilt journal bearings, and revealed that the greater the tilt angle of journal, the greater the effect of the journal axial speed. Girish et al 5 proposed an innovative form of four‐tile variable bearing structure considering journal tilt. Yang et al 6 studied the effect of journal tilt on hybrid lubrication performance.…”
Section: Introductionmentioning
confidence: 99%